Results of a European-wide external quality assessment (EQA) scheme for rerological detection of anti-SARS-CoV-2 (CoVimm): pitfalls of routine application - Kittel, Maximilian; Eichner, Romy; Aida, Sihem; Bode, Anna; Ast, Volker; Kessler, Anja; Neumaier, Michael; Wölfel, Roman; Haselmann, Verena (Viruses, 2022)
Background: During the last two years, a variety of assays for the serological detection of antibodies to the new SARS-CoV-2 virus have been launched and used as part of standard care in many laboratories. The pace with which these tests have been introduced into routine care emphasizes the importance of quality measures for analytical methods, particularly with regard to the implications of results for clinical and epidemiologic decisions. Accuracy, reliability and comparability of analytical test results are thus essential, and here external quality assessment (EQA) is the most important quality assurance tool. It allows us to achieve harmonization of test methods as a prerequisite for a high standard of performance for laboratory and analytical techniques and their interpretation. Methods: This EQA scheme consisted of pre-characterized clinical biospecimens dedicated to the analysis of anti-SARS-CoV-2 IgG total antibodies and differentiation into spike protein-specific IgG antibodies against SARS-CoV-2 (anti-S-SARS-CoV-2) and nucleocapsid-specific IgG antibodies against SARS-CoV-2 (anti-N-SARS-CoV-2). Results: A total of 239 laboratories across Europe participated in this scheme, called CoVimm. In detail, 536 results for anti-SARS-CoV-2 IgG, 431 results for anti-S-SARS-CoV-2 IgG, and 200 results for anti-N-SARS-CoV-2 IgG were reported. Based on the pre-defined thresholds, the success rates for the determination of anti-S-SARS-CoV-2 IgG and anti-N-SARS-CoV-2 IgG were 96% and 90%, respectively. Interestingly, only 64% of the participating laboratories successfully passed the EQA scheme for the determination of total anti-SARS-CoV-2 IgG. Conclusions: This EQA revealed serious concerns regarding the reliability and appropriate use of anti-SARS-CoV-2 antibody assays in routine care. In addition to the wide heterogeneity of different assays used by participating laboratories, a lack of standardization and harmonization is also evident. This is of particular importance for reliable and clinically meaningful interpretation of test results.